Indiscretions : avant-garde film, video, & feminism - Mellencamp, Patricia (Bloomington : Indiana University Press, 1990)
Indiscretions follows the path of U.S. avant-garde film and video from the underground of the 1960s to the academy of the 1980s. Patricia Mellencamp traces and charts the intersections of Lacanian psychoanalysis and the desiring male subject, Roland Barthes and texts of pleasure, Michel Foucault and the disciplinary society, the grotesque body and Mikhail Bakhtin, the rhizomatic alogic of Gilles Deleuze and Felix Guattari, and the female subject of feminist film theory. She creates a dialogue among theory and popular culture and politics through inventive readings of the films of Owen Land, Hollis Frampton, Ken Jacobs, Bruce Conner, Robert Nelson, Michael Snow, Yvonne Rainer, and Sally Potter, and videotapes by Ant Farm, TVTV, Michael Smith, William Wegman, and Cecelia Condit.
Historically speaking -- Visionary film and sexual difference -- Video politics -- Surveillance and simulation -- Theoretical objects -- Postmodern TV -- Uncanny feminism -- Last scene in the streets of modernism -- Taking a cue from Ariadne -- Images of language and indiscreet dialogues -- The avant-garde, the everyday, and the underground.
Includes bibliographical references (pages 215-231) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Experimental films -- History and criticism; Feminism and motion pictures; Féminisme et cinéma.; Films expérimentaux -- Histoire et critique; PERFORMING ARTS -- Film & Video -- Reference; Experimental films; Feminism and motion pictures; Experimentalfilm; Frauenfilm; Theorie; Experimental films -- United States -- History and criticism; Feminism and motion pictures -- United States; Experimental films -- History and criticism; Feminism and motion pictures; Criticism, interpretation, etc